Etyka języka w świadomości studentów - Święcicka, Małgorzata; Peplińska-Narloch, Monika (Poznańskie Spotkania Językoznawcze, 2014)
The main purpose of the article is to determine the means of functioning of the concept of language ethics in the awareness of the students in Bydgoszcz. The respondents, on the one hand, signal certain questions connected with language ethics and exchange views constituting the elements of a broadly understood language culture, on the other hand, – provide quite extensive and dependable definitions of language ethics, in which they take into consideration various contexts. The students being questioned usually associate the ethics of word with politeness, respect toward the partner of conversation, responsibility for words, dependability and honesty in language contacts. The academic youth clearly places in opposition the language ethics with such notions as a lie or linguistic manipulation, regarding them as unethical.